The complete chloroplast genome of Primula bella (Primulaceae): a species endemic to the Hengduan Mountains in China - Wan Tang; Yushuang Chen; Chenling Zheng; Shuang Xiong; Yuan Huang (Mitochondrial DNA. Part B. Resources)
We sequenced and annotated the complete chloroplast genome of Primula bella (Primulaceae). The 154,775 bp genome displays a typical quadripartite structure: an 85,343 bp large single-copy (LSC) region, a 17,772 bp small single-copy (SSC) region, and two 25,830 bp inverted repeat (IR) regions. It contains 130 genes (86 protein-coding, 36 tRNA, 8 rRNA). Phylogenetic analysis revealed close relationships between P. bella, Primula annulata, and Primula walshii, supporting the monophyly of section Minutissimae. This study provides valuable genomic resources for P. bella and insights into Primulaceae phylogeny.